Political Socialization of the General Election Commission (KPU) of Solok Regency for Novice Voters in the 2020 Regional Elections - Yosi Febriani; Al Rafni; Suryanef Suryanef (CV. Rayyan Dwi Bharata, 2022)
Political socialization for novice voters is crucial, because novice voters are very vulnerable to being influenced by various issues in making political choices. This article aims to find out the form of socialization of the Solok Regency KPU for novice voters in the 2020 Regional Elections in Solok Regency for novice voters. The type of research used is descriptive qualitative. The political socialization carried out by the Solok Regency KPU in socializing the 2020 Regional Elections is through the official website of the Solok Regency KPU, Facebook, Instagram, Tik Tok and Youtube KPU Solok Regency, KPU Goes To School or KPU Goes To Campus as well as direct visit services to the Solok Regency KPU office. There are several obstacles in the socialization activities including lack of human resources, budget constraints, limitations due to the covid-19 pandemic conditions, The interest in reading novice voters and the access to schools that will be given socialization is quite far away. Political Socialization affects the political participation of novice voters in election activities. Therefore, it is necessary to strengthen political socialization programs for novice voters